Aerospace series. Shank nuts, self-locking, serrated, in heat resisting steel FE-PA2601 (A286), silver plated. Classification: 1 100 MPa (at ambient temperature) / 650 °C. (30th June 2015) - British Standards Institution,
No abstract available